Manajemen Pendidikan Edutainment di TPA Al Hikmah Kewangunan Petanahan - Sulis Rokhmawanto; Siti Fatimah (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2020)
The focus of the study in this study was motivated by a weakening trend interest in learning in non-formal education, especially religious education, is one of them Al-Qur'an Education Parks, in fact, in almost all places, there are many educational parks, Al-The Qur'an no longer organizes teaching and learning activities because it doesn't exist the santri or on the other hand exist but their existence is only sober, so it is very necessary edutainment-based education. Education based on edutainment in principle education which in its implementation is carried out in ways that are fun, with the aim that students feel happy and comfortable participating in learning. This research is a field research (field research) with a qualitative research type.The selection of sources was carried out using purposive sampling and snowballing sampling techniques.Data collection techniques with techniques: interviews, observation, and documentation. Whereastest the validity of the data using data triangulation techniques in the form of technical and source triangulation. Results this study shows that the first, in the implementation of Edutainment at Tpa AlThe wisdom of Kewangunan Village, Petanahan District, includes four stages, namely planning carried out through three processes, organizing consisting of two groups, mobilization which consists of two forms of mobilization, and supervision which is divided into two forms of supervision. Second, the Implementation of Edutainment Education includes: Making yells opening chants, Singing and music, Magic games and Humorous stories.